Feiyiliu Mixture sensitizes EGFRDel19/T790M/C797S mutant non-small cell lung cancer to osimertinib by attenuating the PRC1/Wnt/EGFR pathway - Shi, Jingjing; Hao, Shaoyu; Liu, Xiantao; Li, Yingying; Zheng, Xin (Frontiers in Pharmacology, 2023)
Osimertinib is a potent epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) for the treatment of patients with EGFR-mutant non-small cell lung cancer (NSCLC). However, the emergence of acquired resistance due to the EGFR-Del19/T790M/C797S mutation limits the clinical application of osimertinib. Feiyiliu Mixture (FYLM), a clinical experience formula of Chinese medicine, was used to treat lung cancer with good clinical efficacy. In this study, we aimed to investigate the mechanism by which FYLM delays osimertinib resistance in EGFR-mutant cell lines and EGFR-mutant cell tumor-bearing mice. The osimertinib-resistant cell models were established in mouse Lewis lung carcinoma (LLC) cells transfected with EGFR-Del19/T790M/C797S mutant lentivirus. In cell experiments, after 48 h of treatment with FYLM-containing serum, MTT assay was used to detect the relative cell viability, and western blotting was used to detect EGFR protein phosphorylation expression. In animal experiments, C57BL/6J mice were subcutaneously injected with LLC cells stably expressing EGFR-Del19/T790M/C797S mutations to construct a xenograft model. After 2 weeks of FYLM and/or osimertinib treatment, the expression of proliferation-related, apoptosis-related and PRC1/Wnt/EGFR pathway markers was detected by real-time qPCR, western blotting and immunohistochemistry. The results showed that when combined with osimertinib, FYLM synergistically reduces proliferation and increases apoptosis to improve drug resistance. In vitro, FYLM-containing serum reduced the EGFR phosphorylation. In vivo, FYLM downregulated the expression of cyclin B1 and Bcl-2 while upregulating the level of cleaved Caspase-3 protein, indicating that FYLM promotes apoptosis. Furthermore, FYLM reduced the expression of p-EGFR, p-Akt, PRC1 and Wnt pathway-related proteins such as β-catenin, c-Myc and c-Jun. In conclusion, the present study identified that FYLM inhibited PRC1/Wnt/EGFR pathway activation, reduced proliferation, and promoted apoptosis, thereby increasing the sensitivity of EGFR-mutant NSCLC to osimertinib. Our study provided a new idea for Chinese medicine to play a role in enhancing efficacy and reducing toxicity in the treatment of NSCLC.